For a new art of living: spaces and reabilitation practices for the visually impaired subjetcs (Research, Society and Development, 2020)
The experience of visual impairment leads to new learning, among which the role of rehabilitation and its repercussions for the understanding of life dynamics stand out. This study aims at Analyzing the spaces and practices of rehabilitation experienced by subjects with visual impairment, immersed in their daily lives. The technique used was that of a focus group and the data obtained were submitted to thematic analysis. The study obtained ethical approval for its realization. As for the results, the themes that emerged from the speeches were: the first steps: the rehabilitational trajectory; relearn to do: the activities of daily life (avd); relearn to move: the steps to orientation and mobility; repressing to read and write: the meeting with braille; and a survey at the percurse: assistant technologies. The study concludes that despite the improvements achieved in the availability of services aimed at the enjoyment of the rights of citizenship and freedom by people with blindness and low vision, obstacles of a political, operational, access and use of technical and technological resources by such individuals still persist. Even so, rehabilitation has proved to be an important tool allied in the resumption of the art of living in the face of blindness.